Product engineering : molecular structure and properties - Wei, James, 1930- (Topics in chemical engineering (Oxford University Press), 2007)
Preface. 1. Product Exploration and Discovery. 2. Product Development to Business. Part II Molecular Structure-Property Relations. 3. Search Challenges and Methods. 4. Theory and Quantitative Predictions. 5. Predictions by Correlations. 6. Estimations by associations and trends. 7. Random Searches. 8. Research Frontiers. Part III. Product Engineering. 9. Marketing. 10. Safety, Health and Environment. 11. Product Design. 12. Product Innovation opportunities.